2014
DOI: 10.5539/hes.v4n5p18
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Accounting Students and the Profession: A Case Study

Abstract: This study addresses the gap between accounting educators and the profession. Research indicates accounting graduates are underprepared for this challenging career. The issue stems from accounting educators who only lecture and accounting students who memorize the information provided in these lectures. Accounting students need opportunities to build their professional skills through learning activities that mimic real-world situations. This qualitative study analyzes the perspectives of advanced accounting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Furthermore, it serves as a critical introduction to diverse populations; but more importantly, it is an introduction to the practice of working with the community. According to Lightweis (2014) "the problem is accounting courses are taught by lecture and through the which learning activities challenge students to understand what lies ahead in the accounting profession".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it serves as a critical introduction to diverse populations; but more importantly, it is an introduction to the practice of working with the community. According to Lightweis (2014) "the problem is accounting courses are taught by lecture and through the which learning activities challenge students to understand what lies ahead in the accounting profession".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academicians view based on theory, while practitioners view based on practical experience and the requirements of business" (Pratama, 2015, p. 19). Lightweis (2014) attributed a large part of this problem to the fact that "accounting educators who only lecture and accounting students who memorize the information provided in these lectures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous researches have been performed to find out the factors leading to CPA examination success in various countries (see for example, USA: Dunn & Hall, 1984;Titard & Russell, 1989;Shbaugh & Thompson, 1993;Campbell, Lindsay, & Foote, 2000;Brahmasrene & Whitten, 2001;Whitten & Brahmassrene, 2002;Howell & Belk, 2003. Cocozza, 2005Howell & Heshizer, 2006;Boone, Legoria, Seifert, & Stammerjohn, 2006;Charron & Lowe, 2009;Lindsay et al, 2009;Metinko & Gray, 2010;Lindquist & Smith, 2013;Lightweis, 2014;Hahn & Fairchild, 2015;Morgan, 2015;Hahn & Fairchild, 2015;Trinkle et al, 2016;Nigeria: Odia & Ogiedu, 2013. Jordan: Momany, 2013Abd-Al-Jaleel & Thaher, 2015.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…They also demonstrated that the success on CPA exam needs hard working students. Lightweis (2014) recommended that accounting professors should apply their experience as an accounting practitioners and construct simulations that portray the challenges in the field. Hahn and Fairchild (2015) provided evidence that schools with AACSB accreditation achieved statistically significantly higher pass rates when compared to each of these groups.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%